2015
DOI: 10.5194/essdd-8-995-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observations of the atmosphere and surface state over Terra Nova Bay, Antarctica using unmanned aircraft systems

Abstract: Abstract. In September 2012 five Aerosonde unmanned aircraft were used to make measurements of the atmospheric state over the Terra Nova Bay polynya, Antarctica, to explore the details of air – sea ice – ocean coupling. A total of 14 flights were completed in September 2012. Ten of the flight missions consisted of two unmanned aircraft systems (UAS) sampling the atmosphere over Terra Nova Bay on five different days, with one UAS focusing on the downwind evolution of the air mass and a second UAS flying transec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The ABL and sea ice properties have already been a subject of several UAV campaigns focusing on the marginal sea ice zone (MIZOPEX; Zaugg et al, 2013), polynyas (Knuth. et al, 2013;Cassano et al, 2015) and ABL structure offshore (deBoer et al, 2018). Another relevant campaign employing UAVs for the observations of stable atmospheric boundary layer over sea ice is "Innovative Strategies for Observations in the Arctic Atmospheric Boundary Layer" (ISOBAR) (Kral et al, 2018) which took place at and off the coast of Hailuoto island (Finland), i.e., the location of the present study.…”
mentioning
confidence: 94%
“…The ABL and sea ice properties have already been a subject of several UAV campaigns focusing on the marginal sea ice zone (MIZOPEX; Zaugg et al, 2013), polynyas (Knuth. et al, 2013;Cassano et al, 2015) and ABL structure offshore (deBoer et al, 2018). Another relevant campaign employing UAVs for the observations of stable atmospheric boundary layer over sea ice is "Innovative Strategies for Observations in the Arctic Atmospheric Boundary Layer" (ISOBAR) (Kral et al, 2018) which took place at and off the coast of Hailuoto island (Finland), i.e., the location of the present study.…”
mentioning
confidence: 94%
“…The British Antarctic Survey was the first to use UAS for Antarctic boundary layer observations with 20 science flights conducted in October andDecember 2007 (P. Anderson, personal communication 2013). Cassano et al (2010Cassano et al ( , 2016b and Knuth et al (2013) describe UAS flights which observed air-sea exchanges in the Terra Nova Bay polynya in 70 the western Ross Sea. The Finnish Meteorological Institute has conducted UAS flights in Dronning Maud Land, Antarctica, at the Aboa research station.…”
Section: Introductionmentioning
confidence: 99%
“…The multitude of applications and missions for these systems indicates their exibility and utility. UAVs have been used extensively for climate research [1], remote sensing, surveying and other missions [2]. This seems to be a natural consequence of the availability of processors with high processing capabilities, high density batteries, low power modems, low-cost MEMS (micro-electro-mechanical systems) sensors and lower cost airframes.…”
Section: Introductionmentioning
confidence: 99%